SARS-CoV-2: Can sunlight exposure reduce the risk of developing severe consequences of COVID-19?. (February 2022) - Muhammad, Jibran Sualeh; Siddiqui, Ruqaiyyah; Khan, Naveed Ahmed
Abstract: Herein it is proposed that sufficient exposure to sunlight (UVB) modulates host gene expression, offering protection against severe consequences of COVID-19. This could be in addition to sunlight (UVB)-mediated protection by directly inactivating the virus and limiting the viral load. It is suggested that inhibition of CCR2, DPP9, HSPA1L, IFNAR2, OAS1, and TYK2 may, in part, explain UVB-mediated protection against severe consequences of COVID-19. Graphical Abstract: ga1